Religious Symbolism and Political Legitimacy: A Critical Analysis of Baitul Muslimin Indonesia (BAMUSI) - Mukhlish Muhammad Maududi; Andi M. Faisal Bakti; Amirkhan Pashayev (JURNAL INDO-ISLAMIKA, 2026)
This study examines how religious symbolism is negotiated within the political communication and da’wah strategies of Baitul Muslimin Indonesia (BAMUSI), an Islamic wing organization affiliated with the Indonesian Democratic Party of Struggle. The research aims to analyze how religious symbolism is used to construct political legitimacy, reduce anti-Islam stigma toward the party among Muslim voters, and generate polarized interpretations between internal and external actors. Using a qualitative approach within a constructivist paradigm, this study applies a case study design based on in-depth interviews, documentation, and interpretative analysis. The findings reveal that BAMUSI negotiates Islamic symbolism through an integrative discourse that positions Islam, nationalism, and Pancasila as compatible identities within Indonesian democracy. Religious symbols are represented not only through rituals and visual attributes, but also through social-religious programs, digital da’wah, and the involvement of Islamic figures to strengthen emotional and symbolic ties with Muslim communities. However, the study also finds that external actors frequently interpret these symbolic practices as political image-building and electoral camouflage rather than substantive religious commitment. This research concludes that religious symbolism in contemporary Indonesian politics functions as a multidimensional arena of meaning negotiation, political legitimacy, audience accommodation, and identity contestation. The study contributes to the development of political communication and Islamic politics scholarship by demonstrating how religious symbolism operates beyond ideological representation and becomes a strategic mechanism for political branding and legitimacy construction in democratic society.